2022
DOI: 10.1038/s43587-022-00263-3
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear morphology is a deep learning biomarker of cellular senescence

Abstract: Cellular senescence is an important factor in aging and many age-related diseases, but understanding its role in health is challenging due to the lack of exclusive or universal markers. Using neural networks, we predict senescence from the nuclear morphology of human fibroblasts with up to 95% accuracy, and investigate murine astrocytes, murine neurons, and fibroblasts with premature aging in culture. After generalizing our approach, the predictor recognizes higher rates of senescence in p21-positive and ethyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 55 publications
7
77
0
Order By: Relevance
“…Previous studies have shown that cellular senescence affects nuclear morphology ( Pathak et al, 2021 ; Heckenbach et al, 2022 ). We therefore sought to characterize nuclear morphology during aging.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that cellular senescence affects nuclear morphology ( Pathak et al, 2021 ; Heckenbach et al, 2022 ). We therefore sought to characterize nuclear morphology during aging.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear area has been demonstrated to expand during senescence [ 10 ]. Our quantitative analysis has indicated that the population of cobalamin-deficient astrocytes differs from the control culture in terms of cell nuclei area, as presented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Heckenbach et al [ 10 ] examined the morphology of cell nuclei in senescent dermal fibroblasts. They provided strong evidence that there is a significant difference in nuclear area between non-senescent and senescent cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several hallmarks of the aging process, abnormalities of nuclear properties are common features of naturally aged and senescent cells in nonneural tissues [4][5][6] . In neural tissues, the abnormal nuclear shape is observed in aging-associated neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%